Inflation Targeting Regimes - Carare, Alina (IMF Working Papers; Working Paper, 2003)
This paper classifies countries that define their monetary policy framework by an inflation target into full-fledged inflation targeters, eclectic inflation targeters and inflation targeting lite regimes. This classification is based on indicators of the clarity and credibility of the commitment to the inflation target. The three regimes can be viewed as corresponding to different welfare maximizing combinations of policy objectives, each conditional on a country's "endowed" level of credibility. The credibility of the regimes is related empirically to structural differences. Policy implications are drawn, especially for emerging market countries aiming at full-fledged inflation targeting.